Can Fixed-Term Contracts Put Low Skilled Youth on a Better Career Path? Evidence from Spain - J. Ignacio Garcia Perez; Ioana E. Marinescu; Judit Vall-Castello (Institute for the Study of Labor (IZA), 2016)
By reducing the commitment made by employers, fixed-term contracts can help low-skilled youth find a first job. However, the long-term impact of fixed-term contracts on these workers' careers may be negative. Using Spanish social security data, we analyze the impact of a large liberalization in the regulation of fixed-term contracts in 1984. Using a cohort regression discontinuity design, we find that the reform raised the likelihood of male high-school dropouts working before age 19 by 9%. However, in the longer run, the reform reduced number of days worked (by 4.5%) and earnings (by 9%).
Keywords: J08; 330; temporary contracts; long-term impact; labour market career